Effect of actual long-term spaceflight on BDNF, TrkB, p75, BAX and BCL-XL genes expression in mouse brain regions. (22nd January 2015) - Naumenko, V.S.; Kulikov, A.V.; Kondaurova, E.M.; Tsybko, A.S.; Kulikova, E.A.; Krasnov, I.B.; Shenkman, B.S.; Sychev, V.N.; Bazhenova, E.Y.; Sinyakova, N.A.; Popova, N.K.
Highlights: Actual spaceflight considerably decreased BCL-XL gene expression in the hypothalamus. Long-term spaceflight significantly increased BCL-XL gene expression in the hippocampus. Actual spaceflight considerably reduced BCL-XL gene expression in the striatum. Shuttle cabin housing also considerably reduced BCL-XL gene expression in the striatum. Long-term spaceflight failed to affect BAX, BDNF, TrkB and p75 gene expression. Abstract: Mice of C57BL/6J strain were exposed to 1-month spaceflight on Russian biosatellite Bion-M1 to determine the effect of long-term actual spaceflight on the expression of genes involved in the processes of neurogenesis and apoptosis. Specifically, we focused on the genes encoding proapoptotic factor BAX, antiapoptotic factor BCL-XL, brain-derived neurotrophic factor (BDNF) and BDNF receptors TrkB and p75. Spaceflight reduced the expression of the antiapoptotic BCL-XL gene in the striatum and hypothalamus, but increased it in the hippocampus. To estimate environmental stress contribution into spaceflight effects we analyzed spaceflight-responsive genes in mice housed for 1 month on Earth in the same shuttle cabins that were used for spaceflight, and in mice of the laboratory control group. It was shown that 1-month shuttle cabin housing decreased BCL-XL gene expression in the striatum but failed to alter BCL-XL mRNA levels in the hippocampus or hypothalamus. Spaceflight failed to alter the expression of the proapoptotic BAX gene in all investigated brain structures, although the insignificant increase of the BAX mRNA level in the hippocampus of spaceflight mice was found. At the same time, shuttle cabin housing produced insignificant decrease in BAX gene expression in the hippocampus. In contrast to the BCL-XL gene, genes encoding BAX, BDNF as well as TrkB and p75 receptors did not respond to 30-day spaceflight. Thus, long-term spaceflight (1) did not affect the expression of genes encoding BDNF as well as TrkB and p75 receptors, (2) produced dysregulation in genetic control of the neuronal apoptosis, (3) implicated BCL-XL as the risk factor for spaceflight-induced behavioral abnormalities.